THE RELATIONSHIP BETWEEN THE CLINICAL MANIFESTATIONS AND THE PRESENCE OF ANTI CYCLIC CITRULLINATED PEPTIDE ANTIBODIES IN VERY EARLY RHEUMATOID ARTHRITIS - Ahmed, Ibrar; Ali, Zafar; Taqweem, Amjad; Alam, Intekhab; Mehboob, Amjad (Journal of Postgraduate Medical Institute, 2011)
Objective: To establish whether the clinical presentation of anti-cyclic citrullinated peptide (Anti-CCP) Methodology: Patients were seen in outpatient department of Lady Reading Hospital Peshawar from February 2009 to February 2011. Participants were included in the current study if they presented within 3 months of symptom onset and fulfilled 1987 ACR criteria for (RA) in the beginning or at some point during an 18 month follow-up. Data were collected on demographic variables and joint symptoms (tender and swollen joint counts). C- reactive protein (CRP), erythrocyte sedimentation rate (ESR), rheumatoid factor and Anti-CCP antibodies status were measured Results: 110 patients were included (57 were Anti-CCP antibodies positive). The Anti-CCP antibodies positive and negative groups were comparable in terms of demographic variables, inflammatory markers,tender and swollen joint counts and 1987 ACR classification criteria. Rheumatoid arthritis factor was detected more in Anti-CCP antibodies positive patients as compared with Anti-CCP antibodies negative patients.(83.3% vs. 35.8%). There was no significant difference in the pattern of joint involvement, except for an increased prevalence of knee joint swelling in Anti-CCP antibodies positive patients (56.1% vs.17.5%). Conclusions: Patients with and without Anti-CCP antibodies present in a similar way, even within three months of clinically apparent disease that eventually develops into Rheumatoid arthritis. antibodies and negative disease are distinct at the earliest clinically apparent phase of disease.